Effect of High-Fidelity Simulation on Clinical Judgment Among Nursing Students. (10th March 2022) - Ayed, Ahmad; Khalaf, Inaam A.; Fashafsheh, Imad; Saleh, Ali; Bawadi, Hala; Abuidhail, Jamila; Thultheen, Imad; Joudallah, Hasan
Introduction: Nursing education needs to be improved in order to bridge the gap between education and clinical practice. However, clinical placements for nursing students are limited and student nurses often take merely an observer role, especially in critical situations. High-fidelity simulation (HFS) is a teaching method that can bridge the gap between education and clinical practice. The purpose of this study was to evaluate the influence of using HFS as a teaching method on clinical judgment among pediatric nursing students at the Arab American University utilizing a bacterial meningitis case scenario. Methods: A quasi-experimental study with a convenience sample of one hundred and fifty baccalaureate nursing students enrolled in a pediatric health nursing course. Nursing students were randomly assigned to high-fidelity simulation experience or traditional methods. The clinical judgment was assessed using Lasater Clinical Judgment Rubric Tool. Results: Results revealed that the high-fidelity simulation experience has improved pediatric nursing students' clinical judgment. The mean clinical judgment differed significantly at post-test in the intervention group after the simulation (t (148) = 7.20, P < .001). Conclusion: The HFS can be an effective tool to provide a safe and effective learning environment for pediatric nursing students, consequently improving their clinical judgment